Customer relationship marketing: Theoretical and managerial perspectives - Malhotra, Naresh K; Agarwal, James (New Jersey World Scientific, 2021)
Customer relationship marketing (CRM) opportunities are embedded in the entire customer journey spanning several touch points across all stages including prepurchase, purchase, and postpurchase stage. Customer relationship marketing evolved from traditional marketing concept and has broadened its scope today, intersecting with the following domains, namely customer buying behavior process models, customer satisfaction and loyalty, service quality, customer relationship management tools and strategies, customer centricity, and customer engagement activities. A comprehensive.